FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN INISIATIF DALAM PENGGUNAAN METODE KONTRASEPSI JANGKA PANJANG - Megawati; Mustika Fitri (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKes Banyuwangi, 2022)
The initiative to use Long-Term Use of Contraceptive Method (LTM) among active family planning participants is still quite low with a percentage of 4.49%, this is due to several factors that influence it’s use such as maternal age, maternal parity, knowledge, husband’s occupation and socio-cultural status. So in fact the target in achieving the use of long-term contraceptive methods has not been met. The Aim was to determine the relationship between age, parity, husband's occupation, socio-culture and the use of LTM at Puskesmas Riau Silip in 2022. The research method uses case control design with a comparison cases and controls (1:1). To determine the relationship between variables used Chi Square test with a confidence level of α = 0,05. The population were all fertile age couples and active family planning participants as many as 3452 participants, while the sample is 310 samples. Based on the result of the study, there were 115 active family planning participants who used LTM (50%). The conclusions was the factors related to the use of LTM include age, parity and knowledge. For active family planning participants, they should have a better understanding of choosing contraceptives according to their family's health and welfare conditions.